The Role of School History Textbooks in Forming Students’ Tolerance - Korytnikova, Nadezhda (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2019)
The article examines the role of school history textbook in the process of formation of tolerance students; discusses the theoretical interpretation of the concept of "tolerance" as tolerance factors of personality traits, analysis the necessity of tolerance as one of the basic principles in the development of teaching and learning materials for the school history textbooks. Survey of theoretical interpretations of the concept of "tolerance" allowed the author to highlight three aspects of this phenomenon: the tolerant worldview as a moral value, the tolerant communication as communicative norms and the tolerant behavior of consolidating strategy. In conclusion are listed skills and abilities, which are the mechanism for the formation of tolerance. They are grouped according to core competencies of history education: general cultural, social, information competence.